Effectiveness of Health Belief Model–Based Psychoeducation in Enhancing Adolescent Mental Health Accessibility - Sembiring, Isyos Sari; Manurung, Basaria; Manurung, Herna Rinayanti; Sinuhaji, Lidya Natalia; Ginting, Perkasa; Pane, Grace Laura Fidela; Zebua, Oktaviani; Pakpahan, Juwita Febriani (Chakra Brahmanda Lentera Institute, 2025)
Background: Adolescent mental health is a growing public health concern, yet behavioral interventions addressing help-seeking barriers remain limited in low-resource settings. While the Health Belief Model (HBM) has been extensively applied to physical health behaviors, its relevance for improving mental health accessibility among adolescents is underexplored. This study aimed to evaluate the effectiveness of HBM-based psychoeducation in enhancing adolescents’ self-awareness, self-efficacy, and emotional regulation. Methods: A quantitative pre-experimental two-group pretest–posttest design was conducted in Bangun Rejo Village, North Sumatra, Indonesia, following the TREND reporting guideline for non-randomized evaluations. Participants included 50 adolescents aged 12–16 years, selected through cluster sampling. Inclusion criteria were residence for at least six months and parental consent, while adolescents with prior psychiatric treatment were excluded. Data were collected using an HBM-based Mental Health Accessibility Questionnaire (Cronbach’s α = 0.87), with self-awareness and self-efficacy as independent variables and mental health accessibility as the dependent variable. Results: The experimental group showed a higher posttest score (87.60 ± 7.45; 95% CI [84.51, 90.69]) compared to the control group (76.48 ± 11.98; 95% CI [71.58, 81.38]). Between-group differences were significant (t(48) = 3.75, p < 0.001, Cohen’s d = 1.06), indicating a large effect size.. Conclusion: HBM-based psychoeducation effectively enhances adolescents’ accessibility to mental health services by improving self-awareness, self-efficacy, and emotional regulation. The findings support incorporating HBM-based approaches into school and community health programs as low-cost, culturally adaptable strategies to promote adolescent mental health in resource-limited settings.